Urgensi Peraturan Daerah Kabupaten Malinau tentang Penempatan dan Perlindungan Tenaga Kerja Lokal: Urgency of Malinau Regency Regional Regulation on Placement and Protection of Local Labor - Evi, Evi Agreta; Syafruddin; Adit, Aditia Syaprillah (Faculty of Law Hang Tuah University, 2025)
This paper aims to analyze the placement and legal protection of local workers through the establishment of Regional Regulations. This research uses normative legal research with statutory and conceptual approaches, using qualitative descriptions and conclusions using the deductive method. The results show that based on the analysis of the provisions of laws and regulations related to the placement and protection of local workers, it is in accordance with the concurrent authority of local governments to regulate the placement and protection of local workers and in order to form good quality and comprehensive local regulations, a critical analysis has been carried out through the three foundations. Philosophical foundation, which provides protection for local workers in improving their welfare. Sociological basis, Malinau Regency is experiencing rapid economic growth characterized by the growth of new industries engaged in various fields so that it has an impact on the need for local workers who have good skills in order to compete with workers from outside the region and Juridical basis, the local government has the right to establish regional regulations and every citizen has the right to work and a decent livelihood for humanity.